Improved Survival and Retinal Function of Aging ZDF Rats in Long-Term, Uncontrolled Diabetes by BGP-15 Treatment - Wachal, Zita; Szilágyi, Anna; Takács, Barbara; Szabó, Adrienn Mónika; Priksz, Dániel; Bombicz, Mariann; Szilvássy, Judit; Juhász, Béla; Szilvássy, Zoltán; Varga, Balázs (Frontiers in Pharmacology, 2021)
Retinal complications of diabetes often lead to deterioration or even loss of vision. This hastens discovery of pharmacological agents able to counterbalance diabetic retinopathy. BGP-15, an emerging small molecule agent, was formerly proven by our workgroup to be retinoprotective on nonobese diabetic animals, Goto-Kakizaki rats. In the present study, we aimed to examine its long-term tolerability or incidental side effects on obese-prone Zucker diabetic fatty (ZDF) rats to further increase the rationale for a future human translation. To make terminal visual status comparable with our other investigations, we also carried out electroretinography (ERG) at the end of the experiment. Our study was started on 16-week-old ZDF rats and lasted for 52 weeks, while BGP was administered daily by gavage. During the 12 months of treatment, 100% of BGP-treated animals survived compared to the non-treated ZDF group, where 60% of the animals died, which was a statistically significant difference. Based on ERG results, BGP-15 was able to counterbalance visual deterioration of ZDF rats caused by long-term diabetes. Some moderate but significant changes were seen in OGTT results and some relationship to oxidative stress by the western blot method: BGP-15 was able to increase expression of HSP70 and decrease that of NFkB in eyes of rats. These were in concert with our previous observations of SIRT1 increment and MMP9 decrement in diabetic eyes by BGP. In summary, not only is BGP-15 not harmful in the long run but it is even able to reduce the related mortality and the serious consequences of diabetes. BGP-15 is an excellent candidate for future drug development against diabetic retinopathy.